Seroepidemiological survey to cell culture rabies vaccines (CCRV) in Brazil - da Silva, Rodrigo Iais [UNESP]; Chaves, Luciana Botelho; dos Ramos Silva, Sandriana; Katz, Iana Suly Santos; Fernandes, Elaine Raniero; Neto, Rene Cunha; Padovani, Carlos Roberto [UNESP]; Modolo, Jose Rafael [UNESP]; Soares Magalhaes, Ricardo J.; Crompton, Holly; Victoria, Cassiano [UNESP] (Elsevier, 2024)
Rabies is a contagious viral disease that can be easily transmitted by the saliva and brain/nervous system tissues of the infected animals, causing severe and fatal encephalitis in both animals and humans. Vaccination campaigns are crucial to combat and prevent rabies's spread in dogs and humans. The Modified Fuenzalida & Palicios vaccines have been widely used since the 70s and have proven effective in producing a solid serological response. Since 2008, the Brazilian Ministry of Health has introduced a Cell Culture Rabies Vaccine (CCRV) for all dog mass vaccination campaigns in Brazil. However, to date, there is limited evidence on the immunologic response of dogs to this type of vaccine in field conditions. The present study evaluated the serological response in dogs vaccinated with CCRV from blood samples of 724 dogs using the Simplified Fluorescence Inhibition Microtest – SFIMT. Dogs with a titer equal to 0.5 IU/mL or above were considered seropositive. The results revealed that 59.12% (428/724) of all dogs tested and 48.49% (32/66) of primo-vaccinated animals were seropositive. The percentage of seronegative animals was higher than seropositive for animals that received a single dose during their life (p < 0.05). The opposite was observed in animals with five or more doses. The results of this study demonstrated that the CCRV vaccines elicit a satisfactory immunological response in field conditions and can constitute an essential population-level preventive strategy as part of annual canine rabies vaccination campaigns. Although its effectiveness has been studied, there is limited evidence of its immunological response in dogs under field conditions. This paper evaluates the serological response to CCRV in dogs vaccinated during mass vaccination campaigns from 2012 to 2017.